Enabling real-time business intelligence : International Workshops, BIRTE 2013 Riva del Garda, Italy, August 26, 2013 and BIRTE 2014, Hangzhou, China, September 1, 2014. Revised selected papers /: International Workshops, BIRTE 2013 Riva del Garda, Italy, August 26, 2013 and BIRTE 2014, Hangzhou, China, September 1, 2014. Revised selected papers. (2015) - Unknown
No abstract available